Highly selective lossy dual-band bandstop filter synthesis and design based on predistortion hybrid dual-band elliptic reflection function - Soeung, S. (Electromagnetics Academy, 2017)
This paper demonstrates a new class of highly selective bandstop filter based on cascading two identical lossy hybrid dual-band bandstop filters of low resonator Q factor. Each filter is synthesized based on multi-stage predistortion reflection mode technique. To demonstrate the approach, 4th order hybrid dual-band elliptic filter network which is a product of elliptic lowpass and highpass network functions has been predistorted and synthesized with low calculated Q factor. The lossy dual-band bandstop filters are fabricated and realized on microstrip planar structure. Both theoretical and experimental results clearly show good agreements with two stopband rejections up to 35 dB for one stage and 50 dB for two stages with passband loss of more than 10 dB. © 2017, Electromagnetics Academy. All rights reserved.